Vasoactive intestinal polypeptide in rat heart atria: the effect of hyperthyroidism - Kuncová, J; Slavíková, J (Physiological research, 2000)
The effects of transient and sustained hyperthyroidism on vasoactive intestinal polypeptide-like immunoreactivity (VIP-LI) levels were studied in the heart atria of developing and adult rats. Newborn rats were divided into 5 groups. Neo-T animals were treated with thyroxine (T4) during postnatal days 1-8 and sacrificed at the age of 60 days. Neo-S rats were treated with T4 during postnatal days 1-60 and sacrificed one day later. Adult-1 and Adult-2 animals received T4 during days 52-60 and were sacrificed 5-6 days and 1 day later, respectively. Control animals were injected with saline. VIP-LI concentrations were determined in extracts from the left and right atria separately. In Neo-S and Adult-2 rats, spontaneous heart rate, the weight of both atria and total T4 serum levels were significantly enhanced, while their body weight was decreased. The ratio atria weight to body weight was significantly increased in all groups except for Adult-1 animals. Hyperthyroidism led to a significant decrease in VIP-LI levels in both atria of Neo-S and Neo-T rats. Hyperthyroidism induced in adult rats also decreased VIP-LI levels in both atria. However, this change was only transient. In conclusion, our data have provided new evidence that hyperthyroidism induced during the early neonatal period interferes with the development of VIP-ergic innervation in rat atria. The period of the first few postnatal days seems to be essential for this effect, since VIP-LI concentrations in 60-day-old animals did not significantly differ between Neo-S and Neo-T atria.
Keywords: potkani Wistar; srdeční síně; Hyperthyroidism; Rats; Female; stárnutí; Animals; ženské pohlaví; krysa rodu Rattus; mužské pohlaví; Male; Rats, Wistar; zvířata; vazoaktivní intestinální peptid; Aging; Vasoactive Intestinal Peptide; Heart Atria; hypertyreóza